Erbium-zirconia-yttria-aluminum co-doped fiber for amplifier and nanomaterial based ultrafast laser applications / Arni Munira Markom - Arni Munira, Markom (2016)
The tremendous growth in telecommunications traffics increased the demand for very high speed, large capacity and long-haul transmission systems. Therefore, a new optical amplifier is required to overcome the limitations of conventional erbium-doped fiber amplifier. Besides optical amplifier, another interest is on pulsed lasers. Pulsed lasers have expanded an incredible attention in recent years as a possible replacement to high-cost and bulk solid state lasers especially for ultrafast technology with pulse duration down to the femtosecond and attosecond region which led to many diverse applications. In this work, a new Zirconia-Yttria-Aluminum co-doped Erbium-doped fiber (Zr-EDF) was investigated as gain medium for amplifier and pulsed laser applications. The fiber is heavily doped with erbium concentration with absorption pump power around 80 dB/m at 980 nm and was fabricated by using modified chemical vapour deposition (MCVD) process. For amplifier application, this fiber can be used to obtain an efficient gain and noise figure for both single- and double-pass configurations. For instance, at optimum length of 1 m for double pass amplifier, the highest gain of 40.3 dB was achieved at 1560 nm with noise figure less than 6 dB for the specific region. Moreover, a high flat-gain of 38 dB with gain fluctuation of ± 1.5 dB was successfully obtained within 1530 to 1565 nm wavelength. The new Zr-EDFA also performed better compared to the amplifiers configured with the previous Zr-EDF with a lower erbium concentration, conventional bismuth-based EDF (Bi-EDF) and the commercial silica-based EDF (Si-EDF). Pulsed Zr-EDF lasers (Zr-EDFLs) were also demonstrated by using various passive methods. A bright and dark pulse Zr-EDFL were delivered by using nonlinear polarization rotation (NPR) technique to generate dual-wavelength with pulse duration of 27 ns and repetition rate of 14.1 MHz. Q-switched pulsed laser was realized by using thulium-doped fiber (TDF) as solid state saturable absorber (SA) fiber. Bright solitons were also obtained by using high nonlinearity SAs of carbon nanotubes (CNTs) and graphene oxide with the generation of ultrashort pulse duration of 770 fs and 600 fs, respectively. Finally, mode-locked Zr-EDFLs operating in dark pulse regime were successfully demonstrated using three types 2D nanomaterials SAs; graphene oxide, graphene film and black phosphorus as the mode-locker.